Development of a Phenomenon-Based Learning E-Worksheet Using Liveworksheets on the Topic of Chemical Equilibrium - Ramadhoni, Aulia Zahro; Herdini, Herdini; Anwar, Lenny (Journal of The Indonesian Society of Integrated Chemistry, 2025)
This study aimed to develop a Phenomenon-Based Learning (PhBL) electronic student worksheet (E-LKPD) on chemical equilibrium using Liveworksheets. The research employed a Research and Development (R&D) approach with the 4D development model (Define, Design, Development, and Disseminate). The study was conducted at SMAN 7 Pekanbaru and SMAN 9 Pekanbaru. Participants included three expert validators, two chemistry teachers, and 20 twelfth-grade students. Material validation results for content feasibility, PhBL characteristics, language feasibility, presentation feasibility, and graphical design were 95%, 97.22%, 91.67%, 95.83%, and 91.67%, respectively, indicating that the product was valid. Media validation results for display feasibility and software utilization were both 100%, and both were categorized as valid. Teacher responses reached 91.07% (very good), and student responses reached 87.31% (very good). Overall, these findings indicate that the developed PhBL-based E-LKPD for chemical equilibrium, using Liveworksheets, is valid and practical for classroom use. Keywords:       E-LKPD, chemical equilibrium, Liveworksheets, Phenomenon-Based Learning.